Business Plan : Puyuh Legacy / Muhammad Khaliq Arrijal Che Kamalruzaman, Muhammad Afiq Ikmal Abdul and Wan Muhamad Syakib Nordin Aziz - Che Kamalruzaman, Muhammad Khaliq Arrijal; Abdul Aziz, Muhammad Afiq Ikmal; Nordin, Wan Muhamad Syakib (2021)
The following business plan and the feasibility study is for the whole production scenario of local quail at the “Puyuh Legacy” Wakaf Bharu Kelantan. This study includes all theproduction and cost related factors while rearing to marketing of Malaysian quail. At this stage of global populations increase and the demand of protein is increasing quail can be a good source of protein and is very easy to rear and takes short time to be ready. Increasing demand of quail meat and eggs is one of the major reasons to start this farm. This study will help those people who are planning to run quail business around Wakaf Bharu or anywhere in the Kelantan. The primary target of this farm will be the local people of Tumpat and Kota Bharu and the market will be expanded to outside. The area of this entire farm will be 2hectar.